Renal Tubular Acidosis in the Postpartum Period: A Case Report and Literature Review - Carlos E. Duran; Mayra Estacio; Fredy Lozano; Esteban Echeverri; Maria Juliana Riascos; Juan Guillermo Posada; Johanna Schweineberg (Case Reports in Nephrology)
Case Presentation. Distal renal tubular acidosis (dRTA) is characterized by impaired hydrogen ion secretion in the distal nephron resulting either from decreased net activity of the proton pump or from increased luminal membrane hydrogen ion permeability. Typical complications of dRTA include severe hypokalemia, normal anion gap metabolic acidosis, nephrolithiasis, and nephrocalcinosis. The patient is a 25-year-old woman in immediate puerperium with hypokalemia leading to paralysis, and the laboratory findings in this patients were concerning for dRTA. It is rare to encounter this entity during pregnancy, and the impact of this pathology is unknown.